IbM KELOMPOK USAHA BUDIDAYA JAMUR DI KABUPATEN KEDIRI PASCA ERUPSI GUNUNG KELUD - Melanny Ika Sulistyowaty; Juni Ekowati; Achmad Toto Poernomo; M. Faris Adrianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The eruption of Mount Kelud, located in Kediri-East Java that occurred inearly of 2014 resulted damages of some public facilities and also agriculturalland. Most of the people who lived that area are working as farmers andranchers. Many of the villagers became unproductive and could not performactivities of farming and ranching. To solve such a problem, we would like toencourage them by training how to cultivate mushroom Pleurotus ostreatus orknown as â€œTiramâ€ mushroom. The expectation of this activity is they can beindependently economically by cultivating mushrooms in their area after theeruption of Mount Kelud.Keywords: Pleurotus spp, eruption, cultivate, Tiram mushroom, Kediri